PENERAPAN STANDAR PELAYANAN KEFARMASIAN PADA APOTEK KIMIA FARMA DI KOTA KOTAMOBAGU - Boky, Harmita; Lolo, Widya Astuty; Jayanto, Imam (UNIVERSITAS SAM RATULANGI, 2021)
ABSTRACTPharmaceutical serviced have an important role in creating quality health to improve the quality of life of patients. The research purposed to measure the percentage of compliance wit the implementation of pharmaceutical serviced at Kimia Farma Pharmacy in Kotamobagu City, based on the Regulation of the Indonesia minister of health regulation Number 73/ 2016. This research used quantitative method with descriptive approach. The population in this study were all Kimia Farma Pharmacy in Kotamobagu City. The sampling technique used was saturated sampling Data were obtained through observation and filling out questionnaires. Based on the research results, it is known that the resource management of Pharmacy A, B, C has a percentage of 96% and Pharmacy D of 92%. The percentage of pharmaceutical services at Pharmacy A and C is 100%, Pharmacy B is 97% and Pharmacy D is 87%. Based on the research results, it is known that all Kimia Farma pharmacies in Kotamobagu City are categorized as good, including the aspects of resource management and clinical pharmacy services. Keywords : Pharmacy, Pharmacist, Pharmaceutical Service Standards ABSTRAKPelayanan kefarmasian berperan penting dalam mewujudkan kesehatan yang bermutu untuk meningkatkan kualitas hidup pasien. Penelitian ini bertujuan untuk mengukur persentase kesesuaian penerapan standar pelayanan kefarmasian di Apotek Kimia Farma di Kota Kotamobagu berdasarkan Peraturan Menteri Kesehatan Rupublik Indonesia Nomor 73 Tahun 2016. Penelitian ini merupakan jenis penelitian deskriptif. Populasi dalam penelitian ini ialah seluruh Apotek Kimia Farma di Kota Kotamobagu.Teknik pengambilan sampel yang digunakan adalah sampling jenuh. Pengambilan data melalui observasi langsung dan pengisian kuesioner. Berdasarkan hasil penelitian, diketahui pengelolaan sumber daya Apotek A, B, C memiliki persentase sebesar 96 % dan Apotek D sebesar 92 %. Persentase pelayanan kefarmasian pada Apotek A dan C sebesar 100%, Apotek B sebesar 97 % dan Apotek D sebesar 87 %. Berdasarkan hasil penelitian ini diketahui bahwa seluruh apotek Kimia Farma di Kota Kotamobagu dikategorikan baik yang meliputi aspek pengelolaan sumber daya dan pelayanan farmasi klinik. Kata kunci : Apotek, Apoteker, Standar Pelayanan Kefarmasian